Influência da dexmedetomidina/atropina sobre as alterações da variação de pulso induzidas pela hemorragia seguida por reposição volêmica em cães anestesiados com isoflurano - Diniz, Miriely Steim [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate the effects of dexmedetomidine on pulse pressure variation (PPV) changes induced by hemorrhage followed by volume replacement (VR) during isoflurane anesthesia. In a prospective, randomized crossover study, 8 adult dogs (19.5 to 29.2 kg) were anesthetized with 1.3 times the minimum alveolar concentration of isoflurane alone or isoflurane/dexmedetomidine (2 μg/kg/h) (2-week washout intervals). Atropine (0.03 mg/kg IM and 0.01 mg/kg IV) was administered 30 minutes prior to hemorrhage in the dexmedetomidine treatment. In both treatments neuromuscular blockade was produced by atracurium (0.3 mg/kg bolus, followed by 0.3 mg/kg/hour) for performing volume controlled ventilation (tidal volume: 12 mL/kg, inspiration to expriation ratio: 1:1.3 and respiratory rate: 16-20 breaths/min) with a positive end-expiratory pressure of 7 cm H2O. After recording baseline data, progressive withdrawal of 10, 20, and 30% of the estimated blood volume (HV10, HV20, and HV30, respectively) was followed by VR with autologous blood in the same proportion (RV10, RV20, and RV30, respectively). In 4/8 isoflurane-anesthetized dogs hemorrhage induced hypotension [mean arterial pressure (MAP) < 60 mmHg]. Based on MAP changes after hemorrhage during isoflurane anesthesia, dogs were divided in hypotensive (HG) and normotensive groups (NG). During isoflurane anesthesia (HG and NG), stroke index and cardiac index were significantly (P < 0.05) decreased from baseline after hemorrhage, while VR normalized or significantly increased these variables. The PPV (%) was increased by hemorrhage [from 7 (9, 5) (baseline) to 20 (27, 12) and 27 (40, 17) at HV20 and HV30, respectively] [mean (upper, lower ranges)] only in isoflurane-anesthetized dogs that became hypotensive; PPV returned to baseline after VR. Dexmedetomidine caused sustained increases in systemic vascular resistance (HG and NG), and prevented the ...

O objetivo do presente estudo foi avaliar o efeito da dexmedetomidina sob a variação da pressão de pulso (VPP) induzida pela hemorragia seguida por reposição volêmica (RV) em cães anestesiados com isoflurano. Em um estudo prospectivo, aleatorizado e cruzado, 8 cães adultos (19,5 a 29,2 kg) foram anestesiados com 1,3 de concentração alveolar mínima de isoflurano isolado isoflurano associado a infusão contínua de dexmedetomidina (2 μg/kg/h) com intervalo de 2 semanas entre os tratamentos. Administrou-se atropina (0,03 mg/kg pela via intramuscular, IM e 0,01 mg/kg pela via intravenosa, IV) 30 minutos antes da hemorragia no tratamento dexmedetomidina. Em ambos os tratamentos produziu-se bloqueio neuromuscular com atracúrio (bolus de 0,3 mg/kg, seguido por 0,3 mg/kg/hora) para realização de ventilação com volume controlado (volume corrente: 12 mL/kg, relação inspiração/expiração: 1:1,3, frequência respiratória de 16-20 mov/min) com pressão positiva no final da expiração de 7 cmH2O. Após a mensuração dos parâmetros no momento basal, iniciou-se a retirada progressiva de sangue na proporção de 10, 20 e 30% do volume total estimado (HV10, HV20, HV30, respectivamente), e na sequência realizou-se a reposição volêmica com sangue autólogo na mesma proporção (RV10, RV20 e RV30, respectivamente). Quatro dos 8 cães anestesiados com isoflurano apresentaram hipotensão [pressão arterial média (PAM) < 60 mmHg]. Com base nas alterações da PAM após a hemorragia nos cães anestesiados com isoflurano, os cães foram divididos em dois grupos: hipotenso (GH) e normotenso (GN). Durante a anestesia com isoflurano (GH e GN) o índice sistólico (IS) e o índice cardíaco (IC) reduziram-se significativamente (P < 0,05) em relação aos valores basais, enquanto após a reposição volêmica estas variáveis retornaram aos valores basais ou apresentaram aumento significativo. A VPP (%) [média (valores máximo e mínimo)] ...
Keywords: Cão - Doenças; Atropina; Pulso - Medição; Anestesia animal; Anestesicos - Efeito fisiologico; Pulse Measurement